2017
DOI: 10.1007/s00253-017-8362-x
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater contamination with 2,6-dichlorobenzamide (BAM) and perspectives for its microbial removal

Abstract: The pesticide metabolite 2,6-dichlorobenzamide (BAM) is very persistent in both soil and groundwater and has become one of the most frequently detected groundwater micropollutants. BAM is not removed by the physico-chemical treatment techniques currently used in drinking water treatment plants (DWTP); therefore, if concentrations exceed the legal threshold limit, it represents a sizeable problem for the stability and quality of drinking water production, especially in places that depend on groundwater for drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 60 publications
2
39
0
Order By: Relevance
“…3C) pose a potential risk to groundwater. Poorly drilled or maintained deep groundwater wells are subject to the downward transmission of water carrying microbiological and hazardous anthropogenic contaminants [74][75][76] . www.nature.com/scientificreports/ Microbiological and anthropogenic chemical pollution is methodically monitored and regulated in drinking water by law.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3C) pose a potential risk to groundwater. Poorly drilled or maintained deep groundwater wells are subject to the downward transmission of water carrying microbiological and hazardous anthropogenic contaminants [74][75][76] . www.nature.com/scientificreports/ Microbiological and anthropogenic chemical pollution is methodically monitored and regulated in drinking water by law.…”
Section: Discussionmentioning
confidence: 99%
“…The Directive of the European Parliament and of the Council on the protection of groundwater against pollution and deterioration (2006/118/EC) imposes EU member states to terminate exploitation of water from groundwater wells if active substance of any pesticide, including its relevant metabolites, degradation and reaction products exceeds the 100 ng/L threshold 77 . Threshold violations have been reported in Italy, the Netherlands, Belgium, Sweden, Finland and Denmark, leading to the closure of many drinking water wells 74 .…”
Section: Discussionmentioning
confidence: 99%
“…The overall aim of the present study was to test the feasibility of growing fungi for the purpose of metabolizing recalcitrant compounds, utilising part of the fungal species' diversity in Northern European forests and evaluating their growth and survival on relevant Ncontaining recalcitrant compounds. We wanted to screen a larger number of fungal species with varying taxonomy and ecology, and as a first step we performed a screening study using [31]. After the screening study a sub-set of species that showed the best growth was chosen for a simulated process water experiment containing both 2-diethylaminoethanol and N 3 -trimethyl(2oxiranyl)methanaminium chloride.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, groundwater is an important drinking water resource and BAM contamination results in either costly closure of extraction wells or the inclusion of expensive remediation modules such as activated carbon filtration in drinking water treatment plants (DWTPs) 5 . Bioremediation of BAM-contaminated groundwater was suggested as an environmentally friendly and cost-effective alternative treatment method in DWTPs 1,6 .…”
Section: Introductionmentioning
confidence: 99%
“…MSH1 survives well under oligotrophic conditions encountered 3 in DWTPs , develops biofilms , and mineralises BAM at trace concentrations 8 . The strain is considered a prime biocatalyst for treating BAM-contaminated groundwater in DWTPs by bioaugmentation of dedicated filtration modules 1 . Promising results were obtained in both laboratory and pilot-scale studies with bioaugmented sand filters, showing BAM removal below the EU threshold for five to six weeks 11,12 .…”
Section: Introductionmentioning
confidence: 99%